Propriedades ópticas e elétricas de pontos quânticos semicondutores de InAs - Andreza Germana da Silva (2008)
In the present work, we report on the electrical and optical properties ofInAs self-assembled quantum dots in two different situations. First, we perfomed magnetotunneling measurements in stacked self-assembled quantum dot multilayers, with applied magnetic fields up to 12 T. We observe tunneling between quantum dot states in adjacent layers and at high magnetic fields we show evidence of tunneling through Zeeman- splitted quasi-zero dimensional states. Our results imply that the g factors between quantum dots in adjacent layers are strongly affected by the amount of confinement. In the second part of the work, we investigated single GaAs/AlGaAs pillars containing InAs quantum dots by microphotoluminescence. We measured circular pillars of different diameters and studied experimentally the effect of the quantum dot dipole orientation on the intensity of the photonic modes of microcavity pillars, with special attention to the higher energy modes. Our results imply that a percentage of the dots in our pillars has a significant degree of linear polarization, an assumption that has been experimentally confirmed.